2021
DOI: 10.3390/su132212586
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Cause Analysis of Shallow Groundwater Hydrochemistry in the Plains of Henan Province, China

Abstract: With the development of the human population and society, groundwater environmental problems have become an important factor limiting global socioeconomic development, and the study of groundwater hydrochemical characteristics and pollution is a current hot issue. In this study, data regarding shallow groundwater quality in 76 instances were used to evaluate the quality of shallow groundwater in the plains of Henan Province, China, by using a combination of subjective and objective assignments, mathematical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…When both CAI-I and CAI-II are greater than zero, it indicates forward cation exchange adsorption. Conversely, when both CAI-I and CAI-II are less than zero, it indicates reverse cation exchange adsorption (Sun et al, 2021). Through calculation, it is found that approximately 69% of groundwater points exhibit CAI-I and CAI-II values greater than zero.…”
Section: Fig5 Correlation Diagram Of Main Ions To Groundwater In Pong...mentioning
confidence: 98%
“…When both CAI-I and CAI-II are greater than zero, it indicates forward cation exchange adsorption. Conversely, when both CAI-I and CAI-II are less than zero, it indicates reverse cation exchange adsorption (Sun et al, 2021). Through calculation, it is found that approximately 69% of groundwater points exhibit CAI-I and CAI-II values greater than zero.…”
Section: Fig5 Correlation Diagram Of Main Ions To Groundwater In Pong...mentioning
confidence: 98%
“…As part of the natural water cycle, groundwater, stored within the lithosphere, engages in dynamic interactions with its surrounding environment. These interactions involve the exchange of substances and energy, which significantly influence the chemical composition of the groundwater [1][2][3]. The ion concentration in groundwater not only mirrors processes such as carbonate weathering, silicate weathering, and ion exchange during groundwater flow, but also acts as a vital tracer for deciphering groundwater circulation pathways.…”
Section: Introductionmentioning
confidence: 99%